2013
DOI: 10.1126/scitranslmed.3005958
|View full text |Cite
|
Sign up to set email alerts
|

TCR-Ligand k off Rate Correlates with the Protective Capacity of Antigen-Specific CD8 + T Cells for Adoptive Transfer

Abstract: Adoptive immunotherapy is a promising therapeutic approach for the treatment of chronic infections and cancer. Thereby, T cells within a certain range of high avidity for their cognate ligand are believed to be most effective. T cell receptor (TCR) transfer experiments indicate that a major part of avidity is hard-wired within the structure of the TCR. Unfortunately, rapid measurement of structural avidity of TCRs is difficult on living T cells. We developed a technology, where dissociation (koff-rate) of trul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
135
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 98 publications
(149 citation statements)
references
References 29 publications
3
135
0
1
Order By: Relevance
“…Because TCRpMHC interactions typically exhibit weak affinities and fast dissociation rates, this has long precluded conclusive measurements with monomeric pMHCs (10). Nauerth and colleagues (11) recently measured monomeric TCR-pMHC dissociation kinetics using reversible Streptamers and reported that virus-specific CD8 þ T cells with longer half-lives (low k off ) conferred increased functional avidity and better in vivo protection than T cells exhibiting shorter t 1/2 (high k off ). However, the Streptamer assay (11) needs a significant lag time until monomeric TCR-pMHC dissociation starts to become detectable, limiting thereby off-rate analyses to antigen-specific T cells of relative long half-lives, typically found in immune responses against pathogens.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because TCRpMHC interactions typically exhibit weak affinities and fast dissociation rates, this has long precluded conclusive measurements with monomeric pMHCs (10). Nauerth and colleagues (11) recently measured monomeric TCR-pMHC dissociation kinetics using reversible Streptamers and reported that virus-specific CD8 þ T cells with longer half-lives (low k off ) conferred increased functional avidity and better in vivo protection than T cells exhibiting shorter t 1/2 (high k off ). However, the Streptamer assay (11) needs a significant lag time until monomeric TCR-pMHC dissociation starts to become detectable, limiting thereby off-rate analyses to antigen-specific T cells of relative long half-lives, typically found in immune responses against pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…However, the Streptamer assay (11) needs a significant lag time until monomeric TCR-pMHC dissociation starts to become detectable, limiting thereby off-rate analyses to antigen-specific T cells of relative long half-lives, typically found in immune responses against pathogens. Moreover, accurate measurements of TCR-pMHC binding parameters on living T cells (11)(12)(13)(14) require specialized equipment, which is currently not available for the high-throughput screen of antigen-specific T-cell populations.…”
Section: Introductionmentioning
confidence: 99%
“…pMHC molecules for generation of reversible multimers were refolded and multimerized as described previously (7). All pMHC molecules used for the k off -rate assays in this report were conjugated to Alexa488 maleimide fluorophore (Thermo fisher) and multimerized Streptactin APC (IBA).…”
Section: Multimer and Antibody Stainingmentioning
confidence: 99%
“…Human CMV-specific T cell clones and murine T cell lines were generated as described previously (7). Peripheral blood was obtained from a healthy adult donor (male).…”
Section: Cellsmentioning
confidence: 99%
See 1 more Smart Citation